2015
DOI: 10.1155/2015/261329
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with Stigma: Experiences of Persons Affected by Disabilities and Leprosy

Abstract: Persons affected by leprosy or by disabilities face forms of stigma that have an impact on their lives. This study seeks to establish whether their experiences of stigma are similar, with a view to enabling the two groups of people to learn from each other. Accounts of experiences of the impact of stigma were obtained using in-depth interviews and focus group discussion with people affected by leprosy and by disabilities not related to leprosy. The analysis shows that there are a lot of similarities in impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
86
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(90 citation statements)
references
References 23 publications
2
86
0
2
Order By: Relevance
“…The selection, training and supervision of the lay and peer counsellors was crucial. They required specialist knowledge and it was still difficult for some counsellors to become effective [37], pointing to the need for more research on how to improve the selection and training of lay and peer counsellors. A counselling intervention needs to be sustainable, and since this intervention proved to be less sustainable than we hoped it will be vital to strengthen effective links between health professionals and lay and peer counsellors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection, training and supervision of the lay and peer counsellors was crucial. They required specialist knowledge and it was still difficult for some counsellors to become effective [37], pointing to the need for more research on how to improve the selection and training of lay and peer counsellors. A counselling intervention needs to be sustainable, and since this intervention proved to be less sustainable than we hoped it will be vital to strengthen effective links between health professionals and lay and peer counsellors.…”
Section: Discussionmentioning
confidence: 99%
“…An exploratory study was conducted (see [3,10,37]) and based on its findings a counselling practice was drafted and piloted, which led to the Rights-Based Counselling Module (RBCM) (see Box 1). This module can be managed by lay and peer counsellors.…”
Section: Methodsmentioning
confidence: 99%
“…The work of Nilforoushzadeh et al [15] shows that providing psychological care contributes effectively to improve the psychological and social well-being of these patients, and enhances their commitment to follow courses of treatment. Lusli et al [16,17] showed the benefit of psychosocial support like counselling on the leprosy-related stigma. Moreover, Peters et al [18,19] illustrated the success of a contact intervention in Indonesia to reduce leprosy-related stigma in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Although in Bahasa Indonesia there is no direct translation for the term 'stigmatisation' (Lusli et al 2015), the general meaning of a negative label was commonly understood. The anonymous questionnaire suggested a picture in which society (which here referred to formal government policies and practices) did not stigmatise but where stigmatisation was relatively common amongst teachers' own colleagues.…”
Section: Interview Methodsmentioning
confidence: 99%